Pengaruh Penanaman Modal Dalam Negeri, Penanaman Modal Asing, Pendidikan terhadap Penyerapan Tenaga Kerja di Indonesia - Ilham Akbar Pratama; Ali Anis (Jurnal Kajian Ekonomi dan Pembangunan, 2022)
This study aims to determine analyze: (1) relationship between the of domestic on Indonesian investmen employment, (2) relationship between the inpact of forigen investmen on Indonesian employetment (3) relationship of the influence of education on employment in Indonesia. This type of survey is a descriptive surveyand data, used is panel-styel secondary data from 2010 to 2019 obtained from related institutions and agencies. In this study, the panel data regression analysis model was peocessed using eviews. The results obtainet indicate that: the findings of this according to the survey, domestic invesment has appositive and significant effect on employment and forigen invesment has a positive and significant effect. While education has a positive and significant effect. To the absorption of labor.